2020
DOI: 10.1111/aos.14676
|View full text |Cite
|
Sign up to set email alerts
|

Massive submacular haemorrhage in polypoidal choroidal vasculopathy versus typical neovascular age‐related macular degeneration

Abstract: Purpose To investigate the incidence rate of massive submacular haemorrhage (SMH) and risk factors in polypoidal choroidal vasculopathy (PCV) and typical neovascular age‐related macular degeneration (tnAMD). Methods A total of 465 patients who were diagnosed with either PCV (n = 245) or tnAMD (n = 220) from 2003 to 2014 were enrolled. Cumulative incidence of massive SMH in PCV and that in tnAMD were compared. Risk factors of massive SMH were also analysed. Results Massive SMH occurred in 32 patients (13.1%) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The current study revealed that the BCVA of PCV was significantly better than that in the other groups throughout the study period, whereas the BCVA of tnAMD did not improve significantly from baseline to final visit. Many studies have shown that the visual prognosis is better in PCV than in tnAMD [ 29 ] although PCV is well known for its hemorrhagic nature [ 5 ]. In this study, multivariate analysis showed that better final BCVA was significantly associated with younger age, better baseline BCVA, and not diagnosed as tnAMD; these factors are characteristic of PCV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study revealed that the BCVA of PCV was significantly better than that in the other groups throughout the study period, whereas the BCVA of tnAMD did not improve significantly from baseline to final visit. Many studies have shown that the visual prognosis is better in PCV than in tnAMD [ 29 ] although PCV is well known for its hemorrhagic nature [ 5 ]. In this study, multivariate analysis showed that better final BCVA was significantly associated with younger age, better baseline BCVA, and not diagnosed as tnAMD; these factors are characteristic of PCV.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascular age-related macular degeneration (nAMD) and retinal arterial macroaneurysm (RAM) are two major causes of SMH [ 1 3 ]. In Asia, polypoidal choroidal vasculopathy (PCV), which is a subtype of nAMD characterized by polyp-like choroidal vascular dilation, is frequently associated with SMH [ 4 , 5 ]. Polyp regression is important for the prevention of SMH, and various clinical studies have shown that anti-vascular endothelial growth factor (VEGF) therapy is effective for PCV [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the development of anti-vascular endothelial growth factor (VEGF) intravitreal injections (IVI), which considerably improved the visual prognosis of neovascular AMD (nAMD), submacular hemorrhage (SMH) remains a rare complication associated with a poor visual prognosis. 2 Therefore, identifying clinical and morphological factors for SMH could help preventing their occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] It is believed that polypoidal lesion regression is important because polypoidal lesions that remain perfused are a potential source of J o u r n a l P r e -p r o o f disease activity, and may subsequently develop large subretinal hemorrhages, with resultant severe loss of vision. [15][16][17][18][19] The EVEREST II study reported that rates of complete polypoidal lesion regression in the combination therapy group was almost double that of the monotherapy group at month 12 (69.3% vs. 37.4%, p<0.001). 8 Among articles that describe polypoidal lesion regression and changes in polypoidal lesion area, the results are typically reported in a dichotomous fashion (for example, polypoidal lesion completely regressed / closed vs. present) or as a mean polypoidal lesion area in each treatment group.…”
Section: Introductionmentioning
confidence: 99%